Consumo intensivo de alcohol y conductas sexuales de riesgo, en el Colegio Bernardo Valdivieso, Tercero de Bachillerato sección matutina - Erique Sigcho, Magdalena Isis (2019)
The purpose of the present investigation was to determine the relationship between intensive alcohol consumption and the risky sexual behaviors of a group of teenagers. Therefore, when analyzing and investigating the problems that exist in our environment, the relevance of carrying out this research with a cross-sectional quantitative approach with a comparative descriptive scope was taken, taking as a sample 180 students between the ages of 16 and 19; the same one that they selected by means of a sampling not probabilistic for convenience. The research was quantitative, transversal and analytical; As data collection instruments, a survey designed (Mamari, A., and Silva., J. 2012) and modified by the researcher based on Sexual Risk Behaviors and the self-applied Alcohol Consumption Test AUDIT was used. Once the instruments were applied, it was found that there is sufficient statistical evidence to affirm that risky sexual behaviors are highly significant with intensive alcohol consumption, that is, the greater the consumption of alcohol, the greater the likelihood of risky sexual behaviors. Keywords: sexual behaviors; contraceptives; Alcohol consumption in young people